If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 1 = x + -26 Reorder the terms: 1 + -7x = x + -26 Reorder the terms: 1 + -7x = -26 + x Solving 1 + -7x = -26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -7x + -1x = -26 + x + -1x Combine like terms: -7x + -1x = -8x 1 + -8x = -26 + x + -1x Combine like terms: x + -1x = 0 1 + -8x = -26 + 0 1 + -8x = -26 Add '-1' to each side of the equation. 1 + -1 + -8x = -26 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = -26 + -1 -8x = -26 + -1 Combine like terms: -26 + -1 = -27 -8x = -27 Divide each side by '-8'. x = 3.375 Simplifying x = 3.375
| x-18+18=77+18 | | 28=5x-7-17x+23 | | 3x-2+8x-22=96 | | 10x^2-45x+20= | | 5(y+4)=y+36 | | .5x+2=-2 | | 7x+5-6x=23 | | 5-3(x-1)=2x-(x+4) | | 3x-5+5x=52 | | .5x+2=0 | | x-16+16=79+16 | | 1-3x+5x=17 | | 6x-2=4+3x-2 | | (2n)(4n+2)= | | X+2(3.5)=7 | | 1+5x-3x=-17 | | .5x+2=1 | | 0.3n=0.2 | | 9+6x-3x=36 | | 2x+2=96 | | 13=1-2x-2x | | 4x-3-2x=-3 | | 26=3c-3(6-2c) | | Vf=vi+(9.81)6 | | 4x-5=-19 | | 7x+1-2x=41 | | 2x^2-4x+6y-10=0 | | -27+6d=7(4d+8) | | 8+4x-3x=-2 | | 13x-31+8x-176=180 | | rt-2n=fort | | 3x-4(x+3)=22 |